PASARSENEN: DARI PASAR MENJADI KAWASAN ELIT - Yusuf, Nur Fadilah (History Department, Faculty of Humanities, University of Jember, 2023)
This article discusses the development of Pasarsenen in four different eras, starting from the era of the Vereenigde Oost-Indische Compagnie (VOC) to the New Order government. Pasarsenen shows its role in building a city and area that has an elite nuance but can be reached and lived in by people from various walks of life. This article also discusses several important events such as infrastructure development and supporting facilities in the city, educational facilities, gathering places for artists to the headquarters of political parties. This study uses historical methods according to Louis Gottschalk, namely heuristics, source criticism, interpretation and historiography. In addition, a geographical approach is used in this article because in it the author discusses the relationship between spatial space and economic, social, political and educational activities. The author uses Location Theory according to Robinson Tarigan which is the analytical knife for the writer in reconstructing this research. The purpose of the author in conducting research from this article is to review how the history of the formation of Pasarsenen, the development of Pasarsenen from time to time and the transformation of Pasarsenen into an elite area in Jakarta. Keywords: Pasarsenen, Development of Ages, Elite Areas, Urban Infrastructure and Facilities